Metadata gamification: Jogos sérios para melhoria de descrição de dados da investigação - Bruno Coelho da Silva (2017)
Metadata consists of a set of data that describes other data facilitating search and categorization. There are numerous research data hosting platforms, and with the proliferation of particular amount of information on the network, increasingly a good rating is required for this not dispersed and become inaccessible to those who want access.In recent years the gamification, the application of gameplay in contexts normally unplayable,has been introduced in order software to increase user interaction with the platform in question.These techniques include complement certain objectives, receive the same reward, compete withother users. [DDKN11a]Dendro is an open-source platform developed by Infolab FEUP, which aims data storage from researchers, encouraging them to use metadata as descriptors, that facilitate the preservation and location of such information.The work order being developed is the use of the particular gamification microarray under Dendro platform in order to make the most satisfying user experience of placing metadata.